Historical globalization and its effects: a study of Sylhet and its people, 1874-1971 - Hossain, Ashfaque (2009)
This thesis examines the effects of 'Historical Globalization' on Sylhet and its people from 1874 to 1971. The aim of the thesis is to show two intersecting worlds within which the people of Sylhet lived their lives. At the local level they have responded to the introduction of the capitalist tea plantation. At the global level they established a 'diaspora' and social networks that maintained contact with the homeland. The dissertation considers the reshaping of Sylhet and its role as buffer zone between Assam and Bengal - the biggest province of British India. Thus it looks at Sylhet's place as the producer of global commodity tea - interfacing capital and labour that left long-term impact. It explores how local people itself becoming global for seeking economic fortune. The dissertation further examines identity politics from 1870s to 1971 as these events shaped political mobilizations at home and abroad that ended up the creation of Bangladesh. The study begins in 1874, when Assam Province was created taking Sylhet from Bengal and ends in 1971, when Bangladesh emerged where Sylhetis played a key role at home and across the globe. The chapter one traces the distinctive nature of Sylhet as a frontier, a meeting point of cultures even before the opening of Sylhet for tea capitalism. Chapter two examines the local and overseas entrepreneurs involved in the development of the plantation. Chapter three focuses on the phenomenon of labour migration within the South Asian context created by the plantation, the recruitment of tea labourers from other regions up to 1000 kilometres away, some affected by famine and a sharp termination of the contacts with their homeland following the partition in 1947. Chapter four explores mobility of labour created by the merchant marine, drawing in Sylheti seafarers with a tradition of migration and involvement in water transport and taking them across the globe. It considers the impact of 1947 partition, cutting off Sylhetis from Calcutta and ships - out migration not only continues but become torrent. Chapter five goes on to examine social improvement through communication, education and public health. Chapter six looks at the political mobilization in Sylhet, the reaction of the Hindu elites to the prospect of decolonization and the displacement of this elite following partition in 1947 and trans-national network of Diaspora nationalism. The Sylhet referendum in 1947 emerged as a watershed needs emphasising more strongly as a structuring element in the overall study.